Cortical responses to noninvasive perturbations enable individual brain fingerprinting - Ozdemir, Recep A.; Tadayon, Ehsan; Boucher, Pierre; Sun, Haoqi; Momi, Davide; Ganglberger, Wolfgang; Westover, M. Brandon; Pascual-Leone, Alvaro; Santarnecchi, Emiliano; Shafi, Mouhsin M. (Brain stimulation, 2021)
In recent years, it has become increasingly apparent that characterizing individual brain structure, connectivity and dynamics is essential for understanding brain function in health and disease. However, the majority of neuroimaging and brain stimulation research has characterized human brain function by averaging measurements from groups of subjects and providing population-level inferences. External perturbations applied directly to well-defined brain regions can reveal distinctive information about the state, connectivity and dynamics of the human brain at the individual level. In a series of studies, we aimed to characterize individual brain responses to MRI-guided transcranial magnetic stimulation (TMS), and explore the reproducibility of the evoked effects, differences between brain regions, and their individual specificity. In the first study, we administered single pulses of TMS to both anatomically (left dorsolateral prefrontal cortex- ‘L-DLPFC’, left Intra-parietal lobule- ‘L-IPL) and functionally (left motor cortex- ‘L-M1’, right default mode network- ‘R-DMN, right dorsal attention network- ‘R-DAN’) defined cortical nodes in the frontal, motor, and parietal regions across two identical sessions spaced one month apart in 24 healthy volunteers. In the second study, we extended our analyses to two independent data sets (n = 10 in both data sets) having different sham-TMS protocols. In the first study, we found that perturbation-induced cortical propagation patterns are heterogeneous across individuals but highly reproducible within individuals, specific to the stimulated region, and distinct from spontaneous activity. Most importantly, we demonstrate that by assessing the spatiotemporal characteristics of TMS-induced brain responses originating from different cortical regions, individual subjects can be identified with perfect accuracy. In the second study, we demonstrated that subject specificity of TEPs is generalizable across independent data sets and distinct from non-transcranial neural responses evoked by sham-TMS protocols. Perturbation-induced brain responses reveal unique “brain fingerprints” that reflect causal connectivity dynamics of the stimulated brain regions, and may serve as reliable biomarkers of individual brain function. •Grand Average TMS evoked potentials (TEPs) do not represent individual response dynamics.•TEPs are reproducible within individuals and specific to stimulated brain regions.•TEPs from multiple regions enable individual brain fingerprinting with perfect accuracy.